Trade-offs between light absorption and energy transfer in a marine light-harvesting complex 2 - Graham P. Schmidt; Dihao Wang; Amala Phadkule; Chern Chuang; Mike Reppert; Gabriela S. Schlau-Cohen (Proceedings of the National Academy of Sciences, 2026)
Purple bacteria are a diverse group of photosynthetic organisms that can capture and convert light energy with high quantum efficiency across a variety of ecological niches. They absorb light via an array of antenna proteins, primarily light-harvesting complex 2 (LH2), and rapidly transport the energy to the reaction center, where charge separation occurs. LH2 typically consists of eight or nine subunits that each contain three bacteriochlorophyll and one carotenoid. In the marine species Marichromatium (Mch.) purpuratum , the LH2 subunits bind an additional carotenoid, boosting absorbance in the blue where the underwater solar spectrum peaks. In order to accommodate the additional carotenoid, LH2 from Mch. purpuratum consists of only seven subunits, unique among known LH2. Using ultrafast transient absorption (TA) spectroscopy, time-resolved fluorescence, and steady-state techniques, we investigated the effects of these structural differences on the energy transfer dynamics of LH2 from Mch. purpuratum . Our results show, relative to other species, significantly slower rates of energy transfer within LH2 and an excited-state manifold likely to also slow energy transfer between LH2. LH2 from Mch. purpuratum is therefore tuned to match the solar spectrum of its ecological niche, suggesting that the variations in the molecular organization of these antenna proteins may be primarily for optimal light absorption.